MOTHER KNOWLEDGE OF NUTRITION AND EFFECT ON NUTRITIONAL STATUS OF CHILDREN IN COMMUNITY HEALTH CENTER - Widiyanto, Juli; Laia, Fitri Sapar (Homes Journal: Hospital Management Studies Journal, 2021)
Background:The level of nutritional knowledge from a mother will affect a person in the decision to provide a child’s intake, so it will automatically affect the nutritional status of the child. Good knowledge is expected that children will get good nutrition so that children’s growth is in accordance with the age of growth and development. Good knowledge of mothers will look to provide or prepare daily food in an amount sufficient for the nutritional needs of the child. Objective:The purpose of this study was to determine the effect of maternal knowledge on nutrition on the nutritional status of toddlers at Puskesmas Harapan Raya Pekanbaru. Method: Thistype of research is observational analytic, with aapproach design cross sectional. The study population was all mothers who have children under five at Puskesmas Harapan Raya Pekanbaru. The research sample consisted of 35 respondents using purposive random sampling technique. The research instrument used a questionnaire to measure the level of knowledge of the nutritional status of toddlers using parameters of body weight / height based on the Z score category. The results of the measurement of research data were then carried out by testing the hypothesis by using the Chi-Square test Result:The results showed that from the results of the hypothesis test the effect of the level of maternal knowledge about nutrition on the nutritional status of toddlers, the value of p = 0.001 (p> 0.05) was obtained, so that Ho was rejected, which means that there was an effect of the level of mother’s knowledge about nutrition on the nutritional status of toddlers. With OR: 14.7 with 95% CI: 2.31-93.44. Conclusion : The level of mother’s knowledge affects the nutritional status of children under five. The magnitude of the influence of a high level of maternal knowledge is 14.7 x fold compared to mothers with low knowledge.